Accuracy analysis of vertical deflection data observed with the Hannover Digital Zenith Camera System TZK2-D - Hirt, Christian; Seeber, G. (Springer - Verlag, 2008)
This paper analyses the accuracy of vertical deflection measurements carried out with the Digital Zenith Camera System TZK2-D, an astrogeodetic state-of-the-art instrumentation developed at the University of Hannover. During 107 nights over a period of 3.5 years, the system was used for repeated vertical deflection observations at a selected station in Hannover. The acquired data set consists of about 27,300 single measurements and covers 276 h of observation time, respectively. For the data collected at an earlier stage of development (2003 to 2004), the accuracy of the nightly mean values has been found to be about 0".10-0".12. Due to applying a refined observation strategy since 2005, the accuracy of the vertical deflection measurements was enhanced into the unprecedented range of 0".05-0".08. Accessing the accuracy level of 0".05 requires usually 1 h of observational data, while the 0".08 accuracy level is attained after 20 min measurement time. In comparison to the analogue era of geodetic astronomy, the accuracy of vertical deflection observations is significantly improved by about one order of magnitude.